Drug-related falls in older patients: implicated drugs, consequences, and possible prevention strategies. (August 2013) - de Jong, Marlies R.; Van der Elst, Maarten; Hartholt, Klaas A.
Falls are the leading cause of injuries among older adults, aged 65 years and older. Furthermore, falls are an increasing public health problem because of ageing populations worldwide due to an increase in the number of older adults, and an increase in life expectancy. Numerous studies have identified risk factors and investigated possible strategies to prevent (recurrent) falls in community-dwelling older people and those living in long-term care facilities. Several types of drugs have been associated with an increased fall risk. Since drugs are a modifiable risk factor, periodic drug review among older adults should be incorporated in a fall prevention programme.